Disproportionate microbial responses to decadal drainage on a Siberian floodplain - Kwon, Min Jung; Tripathi, Binu M.; Göckede, Mathias; Shin, Seung Chul; Myeong, Nu Ri; Lee, Yoo Kyung; Kim, Mincheol (Global change biology, 2021)
Permafrost thaw induces soil hydrological changes which in turn affects carbon cycle processes in the Arctic terrestrial ecosystems. However, hydrological impacts of thawing permafrost on microbial processes and greenhouse gas (GHG) dynamics are poorly understood. This study examined changes in microbial communities using gene and genome‐centric metagenomics on an Arctic floodplain subject to decadal drainage, and linked them to CO2 and CH4 flux and soil chemistry. Decadal drainage led to significant changes in the abundance, taxonomy, and functional potential of microbial communities, and these modifications well explained the changes in CO2 and CH4 fluxes between ecosystem and atmosphere—increased fungal abundances potentially increased net CO2 emission rates and highly reduced CH4 emissions in drained sites corroborated the marked decrease in the abundance of methanogens and methanotrophs. Interestingly, various microbial taxa disproportionately responded to drainage: Methanoregula, one of the key players in methanogenesis under saturated conditions, almost disappeared, and also Methylococcales methanotrophs were markedly reduced in response to drainage. Seven novel methanogen population genomes were recovered, and the metabolic reconstruction of highly correlated population genomes revealed novel syntrophic relationships between methanogenic archaea and syntrophic partners. These results provide a mechanistic view of microbial processes regulating GHG dynamics in the terrestrial carbon cycle, and disproportionate microbial responses to long‐term drainage provide key information for understanding the effects of warming‐induced soil drying on microbial processes in Arctic wetland ecosystems. Decadal drainage on a Siberian floodplain disproportionately altered microbial communities and their functional potential, which corroborated the changes in CO2 and CH4 fluxes between ecosystem and atmosphere. The recovery of metagenome‐assembled genomes (MAGs) demonstrated that CH4 is mostly generated by several novel methanogens, and syntrophy may play an important role in methanogenesis at this site